Synthesis, Characterization, Optical and Dielectric Properties of NiO and Zn-Doped NiO Nanostructures: Toward Advanced Applications - Atizaz Ali; Sohail Ahmad; Muhammad Usman; Nangyaley Khan; Muhammad Hashim; Yasir Ali; Rasool Shah; Naveed Ur Rahman (Advances in Condensed Matter Physics)
In this current study, hydrothermal method was employed to synthesize distinct nanostructures: pure nickel oxide (NiO), Zn-doped NiO, and NiO/ZnO composites. X-ray diffraction (XRD) results confirmed NiO’s cubic structure, with sizes of 17.01 nm for pure NiO and 30.87 nm for composites. Scanning electron microscope (SEM) images revealed flowerlike morphologies, energy-dispersive X-ray spectroscopy (EDX) authenticated the elemental composition without any impurities. Ultraviolet–visible (UV-Vis) spectroscopy demonstrated heightened absorption in doped and nanocomposite samples. The bandgap energy calculated using Tauc’s plot reduced from 2.95 to 2.55 eV with increase in zinc (Zn) content. In Fourier-transform infrared (FTIR) characterization, the Ni–O stretching vibration appeared at 666.7 cm−1 in doped samples, while Zn–O stretching was evident at 586.03 cm−1. Photoluminescence analysis unveiled a strong peak at 470 nm (near band edge) and another at 665 nm (indicative of defects), exhibiting intensified signals in doped and nanocomposite samples due to a higher defect density. The dielectric constant showed increased values at low frequencies attributed to real and space charge polarization. Notably, the conductivity of Zn-doped and nanocomposite samples displayed an upward trend with frequency due to a higher defect density. This study unveils insights into the intricate optical and electrical properties of these novel nanostructures, showcasing their potential in advanced energy storage applications.